2022
DOI: 10.3390/cancers14215241
|View full text |Cite
|
Sign up to set email alerts
|

Novel BH4-BCL-2 Domain Antagonists Induce BCL-2-Mediated Apoptosis in Triple-Negative Breast Cancer

Abstract: Targeting the challenging tumors lacking explicit markers and predictors for chemosensitivity is one of the major impediments of the current cancer armamentarium. Triple-negative breast cancer (TNBC) is an aggressive and challenging molecular subtype of breast cancer, which needs astute strategies to achieve clinical success. The pro-survival B-cell lymphoma 2 (BCL-2) overexpression reported in TNBC plays a central role in deterring apoptosis and is a promising target. Here, we propose three novel BH4 mimetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Previous studies have established a connection between greater tissue hardness in infiltrating lesions within breast masses and an elevated risk of poor patient prognosis [25]. NAC can induce changes in both the internal and surrounding tissues of breast cancer lesions due to the effects of the drugs, leading to alterations in tissue hardness [26]. In our present study, we observed significant changes in the ultrasound elastography parameter SR before and after treatment, while only the group of patients achieving pCR had decreased elastic scores after NAC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established a connection between greater tissue hardness in infiltrating lesions within breast masses and an elevated risk of poor patient prognosis [25]. NAC can induce changes in both the internal and surrounding tissues of breast cancer lesions due to the effects of the drugs, leading to alterations in tissue hardness [26]. In our present study, we observed significant changes in the ultrasound elastography parameter SR before and after treatment, while only the group of patients achieving pCR had decreased elastic scores after NAC treatment.…”
Section: Discussionmentioning
confidence: 99%